WATTY - A Water Surveillance and Cleaning Robot (International Journal of Scientific Research in Science and Technology, 2025)
This paper presents an innovative water surveillance and cleaning system aimed at surveying the water quality in urban water bodies. A real time monitoring and autonomous cleaning mechanism system is developed for water pollution. The surveillance component is a network of sensors to continuously monitor different water quality parameters.